Examining the moderating effects of organisational culture on workplace incivility and psychological well-being at a South African University - Cynthis MARUMA; Mokgata MATJIE; Harriet MALUKA; Fumani MABASA; Andani NETHAVHANI (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: This study aimed to investigate the moderating effects of organisational culture (OC) on workplace incivility (WI) and psychological well-being (PWB) at a higher education institution (HEI) in South Africa. The argument was that the HEI are bureaucratic and hierarchical, which leads to a culture of workplace incivility and if such culture is left unattended, it may become an organisational culture, further affecting victims psychologically Methods: Using quantitative methods, a total sample of 39 probability randomly sampled participants completed both the workplace incivility and psychological well-being questionnaires. Results: Regression analysis showed that the organisational culture positively moderates how workplace incivility affects employees’ psychological well-being. Discussion: Furthermore, the findings revealed that the interaction between WI and OC moderated the effects of WI on employees’ PWB. This, further implies that the participants become acclimatised to the existing and persistent incivility culture to the extent that it does not affect them psychologically anymore. The higher education institution should invest in policies that discourage workplace incivility and provide social support to victims in the organisation thus minimising its potential negative effects on employee psychological well-being.